2022
DOI: 10.1016/j.isci.2021.103697
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss and cystic disease progression in autosomal dominant polycystic kidney disease

Abstract: Summary Progression of autosomal dominant polycystic kidney disease (ADPKD) is modified by metabolic defects and obesity. Indeed, reduced food intake slows cyst growth in preclinical rodent studies. Here, we demonstrate the feasibility of daily caloric restriction (DCR) and intermittent fasting (IMF) in a cohort of overweight or obese patients with ADPKD. Clinically significant weight loss occurred with both DCR and IMF; however, weight loss was greater and adherence and tolerability were better wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 53 publications
1
30
0
Order By: Relevance
“…Mice, mimicking this human mutation, are viable for at least 1 year as homozygotes and have slow progression of PKD. Due to a panel of traits close to human ADPKD (late onset, sex differences, high blood urea nitrogen (BUN), and predominant (~70%) development of cysts in the collecting ducts (CD) of mature mice, this hypomorphic model of ADPKD is widely used in preclinical studies (Hopp, Catenacci, et al, 2022; Hopp et al, 2015; Hopp, Kleczko, et al, 2022; Jamadar et al, 2021; Pastor‐Soler et al, 2022). Our studies provide the first evidence that pannexin‐1 is a specific target in the epithelium of human cysts and aim to show how probenecid inhibits cyst formation in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Mice, mimicking this human mutation, are viable for at least 1 year as homozygotes and have slow progression of PKD. Due to a panel of traits close to human ADPKD (late onset, sex differences, high blood urea nitrogen (BUN), and predominant (~70%) development of cysts in the collecting ducts (CD) of mature mice, this hypomorphic model of ADPKD is widely used in preclinical studies (Hopp, Catenacci, et al, 2022; Hopp et al, 2015; Hopp, Kleczko, et al, 2022; Jamadar et al, 2021; Pastor‐Soler et al, 2022). Our studies provide the first evidence that pannexin‐1 is a specific target in the epithelium of human cysts and aim to show how probenecid inhibits cyst formation in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that these improvements involve mTOR signaling inhibition, AMPK activation, and a reduction in IGF-I supporting restoration of metabolic reprogramming. Accordingly, a clinical trial evaluating the effect of weekly caloric reduction achieved with either caloric restriction or intermittent fasting in 29 overweight/obese individuals with ADPKD was recently completed ( Hopp et al, 2021 ; https://clinicaltrials.gov/ct2/show/NCT03342742 ). The trial was designed as a weight loss intervention based on the prior epidemiological observation that ADPKD progression is faster with higher BMI ( Nowak et al, 2018 ).…”
Section: Cholesterol Reducing Agentsmentioning
confidence: 99%
“…The investigators demonstrated the feasibility of 1-year daily caloric restriction (DCR) and intermittent fasting (IMF) in a cohort of overweight or obese patients with ADPKD. Weight loss occurred with both DCR and IMF, however, weight loss was greater, and adherence and tolerability were better with caloric restriction ( Hopp et al, 2021 ). The study was a pilot and feasibility study, so the sample size was small, and a control group was not included but, according to the investigators, similar annual kidney growth in both groups was observed that was qualitatively low compared to historical controls.…”
Section: Cholesterol Reducing Agentsmentioning
confidence: 99%
“…[6][7][8] Ketogenic dietary interventions (e.g., caloric restriction, intermittent fasting, and classic ketogenic diet) can activate AMPK pathways, improve cellular metabolism, and reduce cyst growth in preclinical models. [9][10][11][12] This section summarizes the rationale, benefits, and safety concerns of these interventions for ADPKD.…”
Section: Metabolic Reprogramming and Rationale Of Dietary Interventio...mentioning
confidence: 99%